Cystine transporter expression is a marker to identify a subpopulation of canine adipose-derived stem cells - ITOH, Harumichi (J Vet Med Sci, 2020)
Adipose-derived stem cells (ADSCs) are promising cell sources for regenerative medicine due to the simplicity of their harvest and culture; however, their biological properties are not completely understood. Moreover, recent murine and human studies identified several functional subpopulations of ADSCs varying in differentiation potential; however, there is a lack of research on canine ADSCs. Cystine transporter (xCT) is a stem cell marker in gastric and colon cancers that interacts with CD44 to enhance cystine uptake from the cell surface and subsequently accelerates intercellular glutathione levels. In this study, we identified a ~5% functional subpopulation of canine ADSCs with xCT(+) expression (xCT(Hi)). Compared with those of the xCT(−) subpopulation (xCT(Lo)), the xCT(Hi) subpopulation showed a significantly higher proliferation rate, higher expression of conventional stem cell markers (SOX2, KLF4, and c-Myc), and higher expression of adipogenic markers (FABP4 and PPARγ). By contrast, the xCT(Lo) subpopulation showed significantly higher expression of osteogenic markers (BMP1 and SPP) than xCT(Hi) cells. These results suggest xCT as a candidate marker for detecting a functional subpopulation of canine ADSCs. Mechanistically, xCT could increase the adipogenic potential while decreasing the osteogenic differentiation potential, which could serve as a valuable target marker in regenerative veterinary medicine.